2024
DOI: 10.3390/jcm13061749
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Application of a Skin Moisturizer Containing Pseudo-Ceramide and a Eucalyptus Leaf Extract on Atopic Dermatitis: A Review

Yutaka Takagi

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease associated with pruritus, an impaired cutaneous barrier function and a disrupted water holding capacity. Levels of ceramides, which are major components of intercellular lipids and are crucial for their functions, are decreased in the stratum corneum of patients with AD. Treatments to increase ceramide levels are effective for AD care. Synthetic pseudo-ceramide (cetyl PG hydroxyethyl palmitamide (SLE66)), which has a structure developed via molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 147 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…Over the last two decades, moisturizer manufacturers have progressed in incorporating bioactive natural ingredients, especially phytochemicals, to improve barrier repair and emollient functions [90]. For example, a topical skin moisturizer incorporated with eucalyptus leaf extract improved skin barrier function of AD patients [91]. A clinical study assessing the role of a non-psychoactive cannabinoid-containing moisturizer demonstrated increased hydration of the skin and improved quality of life in AD patients [92].…”
Section: Carriers Used In Topical Applicationsmentioning
confidence: 99%
“…Over the last two decades, moisturizer manufacturers have progressed in incorporating bioactive natural ingredients, especially phytochemicals, to improve barrier repair and emollient functions [90]. For example, a topical skin moisturizer incorporated with eucalyptus leaf extract improved skin barrier function of AD patients [91]. A clinical study assessing the role of a non-psychoactive cannabinoid-containing moisturizer demonstrated increased hydration of the skin and improved quality of life in AD patients [92].…”
Section: Carriers Used In Topical Applicationsmentioning
confidence: 99%